2017
DOI: 10.1002/adfm.201702513
|View full text |Cite
|
Sign up to set email alerts
|

3D Self‐Supported Fe‐Doped Ni2P Nanosheet Arrays as Bifunctional Catalysts for Overall Water Splitting

Abstract: The development of highly efficient bifunctional electrocatalysts for both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is crucial for improving the efficiency of overall water splitting, but still remains challenging issue. Herein, 3D self-supported Fe-doped Ni 2 P nanosheet arrays are synthesized on Ni foam by hydrothermal method followed by in situ phosphorization, which serve as bifunctional electrocatalysts for overall water splitting. The as-synthesized (Ni 0.33 Fe 0.67 ) 2 P wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
286
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 495 publications
(300 citation statements)
references
References 56 publications
14
286
0
Order By: Relevance
“…Highly efficient water electrolysis generally requires high-performance electrocatalysts with low overpotential, fast kinetics, and high stability. [9][10][11] Recently, transition-metal hydroxides, [7,12] phosphides, [8,[13][14][15][16] nitrides, [17,18] and chalcogenides [19][20][21][22] have been investigated as promising candidates for bifunctional electrocatalysts. [7,8] The search for earth-abundant, lowcost HER and OER electrocatalysts that are robust, have high activity and stability has triggered numerous efforts to replace noble metal-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…Highly efficient water electrolysis generally requires high-performance electrocatalysts with low overpotential, fast kinetics, and high stability. [9][10][11] Recently, transition-metal hydroxides, [7,12] phosphides, [8,[13][14][15][16] nitrides, [17,18] and chalcogenides [19][20][21][22] have been investigated as promising candidates for bifunctional electrocatalysts. [7,8] The search for earth-abundant, lowcost HER and OER electrocatalysts that are robust, have high activity and stability has triggered numerous efforts to replace noble metal-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…The mass transport and diffusion issue during OER should also be considered since it occurs at the triple‐phase boundary regions . To enhance the diffusion of liquid reactants and gas products, directly fabricating the active species with three dimensional (3D) architecture on free‐standing conductive substrates as integrated electrodes has been explored . Concomitantly, the active sites are adequately exposed by constructing 3D nanostructures; the electrochemically active surface area, penetration of electrolyte, and transportation of electron are also increased by the binder‐free characteristic .…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] For example, density functional theory (DFT) calculations show that the sites where Se atoms are at the edges of transition metal selenides are HER active sites. [29][30][31] In this case, it is expected that Exploring highly efficient and low-cost electrocatalysts for electrochemical water splitting is of importance for the conversion of intermediate energy. Indeed, incorporation of heterogeneous metal atoms can induce atomic distortions due to strain and result in additional exposed active sites.…”
mentioning
confidence: 99%
“…[24] Furthermore, it has been shown that the heterogeneous metal atoms doping could optimize the hydrogen adsorption kinetic energy and improve the HER catalytic activity in comparison to monometallic ones. [29][30][31] In this case, it is expected that Exploring highly efficient and low-cost electrocatalysts for electrochemical water splitting is of importance for the conversion of intermediate energy. Moreover, the electronic interaction between each element in mono-cation-doped electrocatalysts has been always ignored.…”
mentioning
confidence: 99%